1990
DOI: 10.1152/jn.1990.64.6.1801
|View full text |Cite
|
Sign up to set email alerts
|

Biosonar behavior of mustached bats swung on a pendulum prior to cortical ablation

Abstract: 1. The biosonar signal (pulse) of the mustached bat, Pteronotus parnellii parnellii, has four harmonics (H1-4), each consisting of a long constant-frequency component (CF1-4) followed by a short frequency-modulated component (FM1-4). As the bat approaches a target, it systematically modifies its pulses to optimize the extraction of information from the echoes. These behavioral responses include 1) Doppler-shift (DS) compensation in which the bat adjusts the frequency of its pulses to correct for the DS in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 0 publications
4
43
0
Order By: Relevance
“…This network potentially includes several midbrain structures, such as the superior colliculus, the periaqueductal gray, and areas laterally and ventrally adjacent to the periaqueductal gray (Suga et al, 1973;Jürgens and Pratt, 1979;Larson and Kistler, 1986;Rübsamen and Betz, 1986;Thoms and Jürgens, 1987;Schuller and Radtke-Schuller, 1990;Kirzinger and Jürgens, 1991;Larson, 1991;Jürgens and Lu, 1993;Gerrits and Holstege, 1996;Schuller et al, 1997;Jürgens, 1998Jürgens, , 2000Jürgens, , 2002Behrend and Schuller, 2000). This midbrain network can function independently from higher-order structures of vocalization control, such as the cingulate cortex (Movchan and Burikova, 1982;Movchan, 1984;Gaioni et al, 1990;Riquimaroux et al, 1992), and lesions at the level of the midbrain dramatically affect sound production in various mammals (Movchan, 1980;Movchan and Burikova, 1982;Kirzinger and Jürgens, 1985;Schuller, 1986;Konstantinov et al, 1988;Jürgens, 1998Jürgens, , 2002. Previously, oftenneglected studies in horseshoe bats suggested that after bilateral ablation of the deep layers of the inferior colliculus and ventrally adjacent portions of the tegmentum including PB, call frequencies emitted at rest and during DSC became less stable and eliminated DSC behavior or even "inverted" the response; instead of decreasing its vocalization frequency in response to increasing echo frequencies, the bat's vocalization frequency increased on average 1 kHz above RF (Movchan, 1984;Konstantinov et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This network potentially includes several midbrain structures, such as the superior colliculus, the periaqueductal gray, and areas laterally and ventrally adjacent to the periaqueductal gray (Suga et al, 1973;Jürgens and Pratt, 1979;Larson and Kistler, 1986;Rübsamen and Betz, 1986;Thoms and Jürgens, 1987;Schuller and Radtke-Schuller, 1990;Kirzinger and Jürgens, 1991;Larson, 1991;Jürgens and Lu, 1993;Gerrits and Holstege, 1996;Schuller et al, 1997;Jürgens, 1998Jürgens, , 2000Jürgens, , 2002Behrend and Schuller, 2000). This midbrain network can function independently from higher-order structures of vocalization control, such as the cingulate cortex (Movchan and Burikova, 1982;Movchan, 1984;Gaioni et al, 1990;Riquimaroux et al, 1992), and lesions at the level of the midbrain dramatically affect sound production in various mammals (Movchan, 1980;Movchan and Burikova, 1982;Kirzinger and Jürgens, 1985;Schuller, 1986;Konstantinov et al, 1988;Jürgens, 1998Jürgens, , 2002. Previously, oftenneglected studies in horseshoe bats suggested that after bilateral ablation of the deep layers of the inferior colliculus and ventrally adjacent portions of the tegmentum including PB, call frequencies emitted at rest and during DSC became less stable and eliminated DSC behavior or even "inverted" the response; instead of decreasing its vocalization frequency in response to increasing echo frequencies, the bat's vocalization frequency increased on average 1 kHz above RF (Movchan, 1984;Konstantinov et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In 3 of the 14 animals, we also tested the effects of the drugs on compensation behavior to natural Doppler-shifted echoes in bats that were swung on a pendulum against a large echo target (Gaioni et al, 1990). For this purpose, the bats are placed in a body mold made from soft foam and attached to the base of the pendulum immediately after the end of drug injections and the injection pipettes had been retracted from the brain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a tactile fovea in the star-nosed mole can be compared with the well-known retinal fovea in other mammals, and also with the acoustic fovea of bats. Moustached bats have a well-characterized acoustic fovea evident from the level of the cochlea [43] to the auditory cortex [44], and Doppler shift compensation behaviour [45] can be considered functionally equivalent to a foveation movement. The existence of a foveaperiphery division of sensory surfaces in the visual, auditory and somatosensory systems of different mammals suggests that this organizational scheme is an efficient general solution to producing a very highresolution sensory system.…”
Section: Discussionmentioning
confidence: 99%
“…However, within the bat's ascending auditory system, single neuron response latencies in the range of 20-25 ms appear as early as the midbrain inferior colliculus [97], which makes it hard to imagine that any more sophisticated and time-consuming cortical processing might be involved in the DSC behavior. Electrical stimulations of the mustached bat anterior cingulate cortex evoked echolocation calls that varied in call frequency over the same range of frequencies as those utilized during DSC [36,37], yet surgical ablation of the so-called "DSC region" of the auditory cortex did not prevent the bats from performing DSC [34]. Where then is the main connection between the ascending auditory and descending vocal motor systems guiding the automated stabilization of echo frequencies?…”
Section: Auditory Feedback Control Of Vocal Pitch In Horseshoe Batsmentioning
confidence: 99%